Poverty in contemporary literature : themes and figurations on the British book market - Korte, Barbara, 1957-; Zipp, Georg (Palgrave Macmillan, 2014)
Poverty and inequality have gained a new public presence in the United Kingdom. At a time of social cuts, new austerity measures and a rhetoric about 'broken Britain', poverty is present in the public imagination, and it is visible in the streets of British cities. Literature can (re- )configure how people think, feel and behave in relation to poverty. This study investigates life-writing, fiction and non-fiction with a poverty theme, produced in Britain from the mid-1990s to the present and contributes to the new transdisciplinary field of poverty studies.